Implementasi Karakter Kristen dalam Menjaga Moralitas dan Kekudusan Hidup sebagai Manusia yang Beradap - Korne Amelia Haba Ito; Yakobus Adi Saingo (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The aim of this author is to discuss the importance of implementing Christian character in maintaining the morality and holiness of life as a civilized human being. This research applies a literature study method where the review is carried out descriptively with supporting material obtained from various literature and the discussion focuses on the author's topic related to the implementation of Christian character in social life. Data was collected from various scientific literature and analyzed reductively which describes the results of the discussion that the implementation of Christian character plays a very important role in maintaining the sanctity of life as a civilized human being which should be implemented from an early age in the current millennial era. It is very important to implement Christian character education, because the teaching is not only limited to understanding theories, but also requires implementing them in the practice of moral behavior and maintaining a holy lifestyle as a long-term investment for the nation and state. As Christians who live in the plurality of the Indonesian nation, we must make Christ a reflection in our behavior, namely the ability to control ourselves and not compromise with sin because Christian values ​​teach that every person needs to realize that this body is God's temple, so that they take the initiative to make themselves a good example. right through the right way of life, words, behavior, social relations, spirituality so that people around them can feel the goodness of the existence of Christians as obedient followers of Christ.